Leveraging Global Stakeholder Relations Paradigm in Managing International Conflicts: The Russia-Ukraine War Example - Daniel Nwanmereni (Randwick International of Social Science Journal, 2026)
Around the globe, there are nations that are in conflict due to one form of incompatibility or the other. The absence of genuine global stakeholders’ commitment to resolve some of these felt conflicts have resulted in avoidable armed conflicts and wars in various regions of the world. Many times, post war reconstruction efforts by global partners hardly heal the infrastructural, economic and psychological devastations caused by international crises. Using the Russia-Ukraine war situation, this paper interrogated the impacts of international crises on nations and people. The study was based on the Relational Dialectics theory which states that the complexities, tensions and conflicting pulls that characterise stakeholder relations due to incompatibilities are opportunities to explore dialogue in the peace-building process rather than contradictions. Being a position article, the paper explored reference materials, especially literature on conflict management processes as the method of study. To forestall the degeneration of international conflicts into major crises, the paper recommended that global partners should demonstrate courage and commitment to wade into international conflicts at felt conflict stages. This will ensure that conditions that could degenerate into serious crises and devastations are nipped in the bud. It was also recommended that the efforts that resulted in the present ceasefire in the Israel-Gaza war amidst heightened devastation and humanitarian conditions, should be replicated to stop other international crises that are plaguing nations and people.